Application of Topsis Method in Employee Performance Assessment at PDAM Bengkulu - Weeildyalihumarita Weeildyalihumarita; Maryaningsih Maryaningsih; Lena Elfianty (Penerbit Jurnal Indonesia, 2021)
Employee performance appraisal is very important, especially for employees in the Bengkulu PDAM environment to encourage employee motivation and professionalism in improving work quality. Constraints faced in conducting performance appraisals are due to the diversity of educational backgrounds, experience, competencies and employee portfolios, so we need a system that can assist in the performance appraisal process, so that Employee Performance Assessment will not take time and get into trouble. In the process of designing a decision support system application for evaluating employee performance using the TOPSIS approach. The TOPSIS method (Technique For Order Performance By Similarity To Ideal Solution) is a multi-criteria decision-making method or alternative choice which is the alternative that has the smallest distance from the positive ideal solution and the largest distance from the negative ideal solution. The implementation of the system uses the Visual Studio 2010 programming language and the method used in this study is the waterfall method. From the results of the tests carried out, it can be concluded that this decision support system can provide the best employee decisions which can later be used as a reference to determine the quality of employee performance.